THE INFLUENCE OF FLEXIBLE WORKING PLACE AND FLEXIBLE WORKING TIME ON JOB SATISFACTION WITH WORK-LIFE BALANCE AS A MEDIATING VARIABLE ON COVID-19 PANDEMIC - Dwira Sena Adila; Pantius Drahen Soeling (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
The aim of this study is to analyze the relation between the flexible working place and flexible working time on job satisfaction, directly or indirectly, with the itervention of the work-life balance as a mediating variable. This research is conducted to a civil servant and a non civil servant/contract-based staff in Indonesian Financial Transaction Reports and Analysis Center (INTRAC). Furthermore, the quantitative approach is used in this research. The data is collected by distributing a questionnaires to 148 respondents and being analyzed with Smart PLS program/application version 3.0 with Sem PLS method. The results concludes that both variables which are flexible working place and flexible working time makes a positive and significant effect on job satisfaction variable. Furthermore the flexible working place and flexible working time on job satisfaction with work-life balance as a mediating variable also have a positive effect. The results of this study explain that the implementation of flexible working place and flexible working time can be said to be successful and has a positive effect on job satisfaction because there is an increase in a work-life balance felt by employees of the Indonesian Financial Transaction Reports and Analysis Center (INTRAC)